Inhibition Zone Test of Chaetomorpha sp. Extract Against Aeromonas hydrophilla and Vibrio sp. Bacteria - Sri Wahyuni; Mohamad Gazali; Ronal Kurniawan (Jurnal Natur Indonesia, 2022)
Chaetomorpha sp. is a green algae that has anti-bacterial compounds and at certain times found very much. The purpose of this study was to see the inhibition zone produced from the ethanol extract of Chaetomorpha sp. against A. hydrophilla and Vibrio sp. This research was done in March 2022. Extraction of Chaetomorpha sp., antibacterial effectiveness testing was done at the Biotechnology Laboratory, Faculty of Fisheries and Marine, Riau University. The method used is descriptive method. Sensitivity test was performed using the Kirby Bauer disc method. To reduce the error rate, it was repeated three times. The doses of macroalgae extract used were, doses of 100% (10,000 ppm), 90% (9,000 ppm), 80% (8,000 ppm), 70% (7000 ppm), 60% (6000 ppm), 50% (5000 ppm), 40% (4000 ppm), 30% (3000 ppm), 20% (2000 ppm), 10% (1000 ppm) and control (Oxytetracycline). Based on the observations, it was found that the use of ethanol extract of Chaetomorpha sp. The result is able to inhibit the growth of bacteria A. hydrophilla and Vibrio sp. at the highest dose (10000 ppm) in an range of 13.5 -14.5 mm which was classified as strong category, the lowest dose was at 5000 ppm as moderate category.